PENGARUH STRUKTUR AKTIVA, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL - Fitriati, Tutut; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this study was to examine the influence of asset structure, profitability, and the size of the companys capital structure, to take the study population are tourism companies, hotels and restaurants listed in the Indonesia Stock Exchange in 2010-2014. Samples were selected using purposive sampling terknik, thus acquired 15 companies (75 firm year) that meet the criteria. Data were analyzed using multiple regression and hypothesis by using SPSS version 21. Based on the results of multiple regression analysis with significance level of 5%, then the results of this study indicate that: (1) The structure of assets affect the capital structure with the value of regression showed a positive relationship or unidirectional, so the first hypothesis can be accepted. (2) Profitability affect the capital structure and show a positive relationship or in the same direction, so that the second hypothesis is rejected. (3) the size of the effect on the companys capital structure, with the value of regression showed a positive relationship in the same direction, so that the third hypothesis can be accepted. Keywords: Structure of assets, profitability, company size, capital structure.